Mitochondrial DNA variants and microbiota: An experimental strategy to identify novel therapeutic potential in chronic inflammatory diseases - Michael Olbrich; Adina-Malin Hartmann; Sven Künzel; Zouhair Aherrahrou; Paul Schilf; John F. Baines; Saleh M. Ibrahim; Misa Hirose (Elsevier, 2024)
We previously demonstrated that mice carrying natural mtDNA variants of the FVB/NJ strain (m.7778 G>T in the mt-Atp8 gene in mitochondrial complex V), namely C57BL/6 J-mtFVB/NJ (B6-mtFVB), exhibited (i) partial protection from experimental skin inflammatory diseases in an anti-murine type VII collagen antibody-induced skin inflammation model and psoriasiform dermatitis model; (ii) significantly altered metabolites, including short-chain fatty acids, according to targeted metabolomics of liver, skin and lymph node samples; and (iii) a differential composition of the gut microbiota according to bacterial 16 S rRNA gene sequencing of stool samples compared to wild-type C57BL/6 J (B6) mice. To further dissect these disease-contributing factors, we induced an experimental antibody-induced skin inflammatory disease in gnotobiotic mice. We performed shotgun metagenomic sequencing of caecum contents and untargeted metabolomics of liver, CD4+ T cell, and caecum content samples from conventional B6-mtFVB and B6 mice. We identified D-glucosamine as a candidate mediator that ameliorated disease severity in experimental antibody-induced skin inflammation by modulating immune cell function in T cells, neutrophils and macrophages. Because mice carrying mtDNA variants of the FVB/NJ strain show differential disease susceptibility to a wide range of experimental diseases, including diet-induced atherosclerosis in low-density lipoprotein receptor knockout mice and collagen antibody-induced arthritis in DBA/1 J mice, this experimental approach is valuable for identifying novel therapeutic options for skin inflammatory conditions and other chronic inflammatory diseases to which mice carrying specific mtDNA variants show differential susceptibility.